An Unheard Variant of Leiomyoma Cotyledonoid Dissecting Leiomyoma: Case Report - Alka Yadav; Sujata Raychauduri; Lakshinder Kaur; Ruchira Wadhwa; Minakshi Bhardwaj (Wolters Kluwer Medknow Publications, 2024)
Leiomyomas are benign smooth muscle tumor of the uterus with varied morphology that are well known to undergo secondary changes. A variety of other unusual patterns of uterine leiomyoma have been described, such as parasitic leiomyoma, cellular leiomyoma, symplastic or bizarre leiomyoma, epithelioid leiomyoma, intravenous leiomyomatosis, and leiomyoma with secondary changes. Some cotyledonoid dissecting leiomyoma (CDL) appears as large fungating masses with widespread extension into the broad ligament and pelvic cavity. Due to its rarity and a clinician's lack of familiarity, such tumors are sometimes misdiagnosed as malignancies. We present a rare case report of CDL. It is a diagnostic challenge for clinicians, pathologists, and radiologists and can be confused with malignancy due to its large size. After extensive literature research, we found 28 case reports of this variant. Little is known in the literature about this entity. We present here a case report of a 65-year-old female emphasizing its clinical, radiological, gross, and microscopic findings. A total hysterectomy was performed on the patient. This tumor does not have malignant potential, but clinicians and pathologists must be aware of its existence to avoid over-treating patients as malignancy.